(3GdeNJGQ ef TYQ GHf GdeYJRs - (3YHO Gddg Hf eMeO GdeYJR HGddg Hf GdeJhcd Hf GdeYJUe Hf GdQTjO GdYHGSj, GHf GdeYJR, CHh GdYHGS,J (B296 (3g` s
(3ChdgG (B:s
(3eG GNJjQ ef TYQ YHOGddg Hf GdeYJR GdaNQ GdCda hSGQjI dG Jed GdHcG LQi OeYgG aj NOhO GdKQi s
(3BNQgG (B:s
(3aj GdHGRj dg hJMSH GdQjT EPG eG fgTG bWfkG Ydi efSQg efaTG hcGf GdaQGZ ef fSGNJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdNW eged GdfbW CMjGfkGs
(3Hjf GdCHjGJ TQhM heYGfjs
(3hGNJdWJ HgG ChQGb ef GdeLehYI aj CTYGQ dZjQ GHf GdeYJR s
(3GdfSNI HgG MhGT s
(3hHChdgG hBNQgG bQGAGJ hJedcGJ JOd Ydi Cf GdeNWhWI jefjIs
(3bQf GdfSN (B:s
Keywords: (3GdCOHs